Association between the ratio of serum creatinine to cystatin C and bone mineral density in Chinese older adults patients with type 2 diabetes mellitus - Gao, Ting; Liu, Fupeng; Ban, Bo; Hou, Yue; Li, Guangxin; Jiang, Mingming; Yang, Qing; Zhang, Mei (Frontiers in Nutrition, 2022)
Background: The ratio of creatinine to cystatin C (Cre/CysC), a marker of muscle function and muscle mass, can be used to predict sarcopenia in different populations. Since sarcopenia is closely associated with osteoporosis, this study investigated the association between Cre/CysC and bone mineral density (BMD) in patients with type 2 diabetes mellitus (T2DM). Method: This cross-sectional study included 391 Chinese patients with T2DM. General information, biochemical indicators, and the BMD of lumbar spine (LS), femoral neck (FN), and total hip (TH) were measured. Results: Pearson correlation analysis showed that Cre/CysC was significantly positively correlated with the BMD of LS (r=0.170, p=0.001), FN (r=0.178, p<0.001), and TH (r=0.205, p<0.001). The results of stepwise linear regression suggested that Cre/CysC proved to be the only biochemical predictor of the BMD at three sites (LS: β= 0. 137, p=0.01; FN: β= 0. 097, p=0. 038; TH: β= 0. 145, p=0.002). Conclusion: In patients with T2DM, high Cre/CysC value is independently associated with low risk of osteoporosis and hence, Cre/CysC may serve as a valuable marker of BMD.